Wrestling injuries during the 2016 Rio and 2020 Tokyo Olympic Games - Shadgan, B.; Molavi, N.; Abaeva, E.; Falahati, S.; Sikimic, S.; Konstantinou, L.; Molnar, S. (British Journal of Sports Medicine, 2024)
Objectives To evaluate and compare the injuries of Olympic wrestlers during the 2016 Rio and 2020 Tokyo Olympic Games held in August 2021 due to the COVID-19 pandemic.